Organic honey from Trás-os-Montes region (Portugal): chemical, palynological, microbiological and bioactive compounds characterization - Estevinho, Leticia M. (2014)
At the present time, the quality, integrity, sanitation and nutritional value of honeys receive attention on an international level due to the increasing content of chemicals in the aforementioned matrix. This work was conducted to evaluate the quality of 75 organic honey samples from the Trás-Os-Montes region (Portugal). Mean values obtained for physico-chemical parameters were: pH 3.7; 15.6% moisture; 0.26 mS/cm electrical conductivity; 0.25% ash; 1.1 mg/kg HMF; 15.3 Gothe diastase activity; 40.3 meq/kg free acidity; 67.8% invert sugars and 2.7% apparent sucrose. All honey samples can be classified as monofloral Erica sp., as showed by pollen features. The amounts of phenols and flavonoids in the samples were also determined. In respect to sanitary quality (fecal coliforms) and safety (sulfite-reducing clostridia and Salmonella), all organic honey samples were negative. Furthermore, yeast and molds were detected in low counts, with mean values obtained of 5.5 cfu/g and the value of total aerobic mesophiles obtained from honeys was established in 1.3 102 cfu/g ± 7.5 101 cfu/g. The levels of flavonoids had a stronger impact on both mesophiles (p = 0.0004) and molds (p = 0.0138) than the sucrose concentration (p = 0.001 and 0.0278; respectively). The results reported in this study should be introduced in the organic honey label, and may help beekeepers, the industry, researchers and consumers better understand honey properties.